2024
DOI: 10.1039/d3cp04316a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing electrocatalytic activity in metallic thin films through surface segregation of carbon

Ayesha Kousar,
Ulviyya Quliyeva,
Ishan Pande
et al.

Abstract: Thin layers of commonly used adhesion metals i.e., Cr and Ti were annealed to investigate and estimate their impact on the electrochemical properties of the carbon nanomaterials grown on top...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…As this is a diffusion-driven process, it will require time. As observed in our recent paper, Cr 2 O 3 serves as an effective diffusion barrier for carbon, which is not formed in the case of CrNi-5 due to the above-discussed delay. Consequently, carbon can infiltrate deeper into the layers, resulting in a more evenly distributed carbon concentration profile and a reduced tendency for surface segregation.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…As this is a diffusion-driven process, it will require time. As observed in our recent paper, Cr 2 O 3 serves as an effective diffusion barrier for carbon, which is not formed in the case of CrNi-5 due to the above-discussed delay. Consequently, carbon can infiltrate deeper into the layers, resulting in a more evenly distributed carbon concentration profile and a reduced tendency for surface segregation.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, in this study, we deposited Ni as a catalyst layer on top of commonly used Ti and Cr adhesion layers on silicon substrates to form CrNi (80 nm of Cr and 20 nm of Ni) and TiNi (20 nm of Ti and 20 nm of Ni) substrates commonly used for growing carbon nanofibers. , These metal layers were annealed at 600 °C for 5 (TiNi-5, CrNi-5) and 20 min (TiNi-20, CrNi-20) in a PECVD chamber (excluding the use of reactive gases and plasma) to mimic the typical ambient conditions during CNF growth. , We then studied the microstructural changes of these commonly used interfacial metal stacks as a result of annealing and attempted to correlate these with their electrochemical activity toward DA and AA. We found that the presence of Ni drastically modifies the microstructure, surface chemistry, and electrochemical activities of Ti and Cr adhesion layers in comparison to that observed in the previous study . Our findings provide a thorough examination of how the Ni catalyst layer alters the microstructure of the Ti and Cr adhesion layers, consequently affecting surface chemistry and electrochemical characteristics.…”
Section: Introductionsupporting
confidence: 50%
See 3 more Smart Citations